The importance of alternative evaluation methods and tools in evaluating the learning of the Arabic language in the elementary school from the teacher's point of view - Al-Qahtani, Adel Abdullah; al-Maliki, Ibrahim Muhammad (Journal of Educational and Psychological Sciences, 2020)
The aim of the research is to identify the reality of Arabic language teachers using alternative evaluation methods and tools in the primary stage, and the researchers used the descriptive analytical approach, and the research tool was to identify the importance of the alternative evaluation in the evaluation of Arabic language learning at the primary stage from the teachers point of view, consisting of (73) (Skill, distributed in seven methods are (performance-based evaluation, communication-based evaluation, observational evaluation, self-evaluation, peer evaluation, evaluation based on student work files (Portfolio), paper and pen evaluation), and the research sample consisted of (200) A teacher, The results showed that the overall mean of the methods in the alternative evaluation questionnaire reached (3.71) with an important degree, and the alternative evaluation method based on performance came first and with an average (3.92) with an important degree, In light of the results, the research recommends preparing a guide for the teacher to use alternative evaluation methods, and that the Ministry of Education take into account alternative evaluation methods when designing Arabic language curricula, and take advantage of the list of alternative evaluation methods in preparing and designing training programs for Arabic language teachers, engaging students to choose strategies that suit them and satisfy their needs.
Keywords: alternative evaluation; Arabic language teachers; primary stage